Mitigating the impact of COVID-19 pandemic on poverty - Celia M. Reyes; Ronina D. Asis; Arkin A. Arboneda; Anna Rita P. Vargas (Philippine Institute for Development Studies (PIDS), 2020)
Poverty simulations suggest that the COVID-19 pandemic and the measures implemented by the government to contain the spread of the virus will increase the number of poor in the country. As such, various social safety nets were implemented by both the national and local government agencies to help the affected individuals, families, and enterprises cope with the economic effects of COVID-19 and to smoothen their consumption particularly during the initial stages of the national lockdown, albeit temporarily.
Keywords: 330; COVID-19; poverty; social amelioration program; Philippines